Sarahisme Posted August 20, 2005 Posted August 20, 2005 is this a 'proof' for this question? [math] h(x) = \sqrt(3 + x) [/math] we want to find a K > 0 such that [math] |h(x) - h(y)| \leq K|x-y| \ \ \forall x,y \in [0,1] [/math] that is we want a K > 0 such that [math] |\sqrt(3 + x) - \sqrt(3 + y))| \leq K|x-y| \forall x,y \in [0,1] [/math] now [math] |\sqrt(3 + x) - \sqrt(3 + y)| = \frac{|(\sqrt(3 + x) - \sqrt(3 + y))(\sqrt(3 + x) + \sqrt(3 + y)|}{|\sqrt(3 + x) + \sqrt(3 + y)|} [/math] [math] =\frac{|(3 + x) - (3+y)|}{|\sqrt(3 + x) + \sqrt(3 + y)|}=\frac{|x-y|}{|\sqrt(3 + x) + \sqrt(3 + y)|} [/math] So, we want: [math] \frac{|x-y|}{|\sqrt(3 + x) + \sqrt(3 + y)|} \leq K|x-y| [/math] The max. value that [math]\frac{|x-y|}{|\sqrt(3 + x) + \sqrt(3 + y)|}[/math] attains is when [math] x=y=0 [/math] So when x=y=0 [math] \frac{|x-y|}{|\sqrt(3 + x) + \sqrt(3 + y)|} = \frac{1}{\sqrt(3)+\sqrt(3)} = \frac{1}{2\sqrt(3)}[/math] So Let K = [math] \frac{1}{2 \sqrt(3)} [/math] [math] \therefore \ if \ \ K = \frac{1}{2\sqrt(3)} [/math] [math] then |\sqrt(3 + x) - \sqrt(3 + y))| \leq K|x-y| \ \ \forall x,y \in [0,1] [/math]
Recommended Posts
Create an account or sign in to comment
You need to be a member in order to leave a comment
Create an account
Sign up for a new account in our community. It's easy!
Register a new accountSign in
Already have an account? Sign in here.
Sign In Now